The Position of Crime Resolution Institutions in Indigenous Peoples in the Identity Politics Perspective - Blasius Mau Kau; Hari Sutra Disemadi; Y Yusriadi (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2020)
One of the demands is to disregard modern justice institutions and utilize customary law as a means to achieve justice for those involved in a criminal offense. But on the other hand, the settlement of the case with customary law turned out to still cause injustice to the victim, and even gave birth to new crimes arising as a result of coercion carried out by the customary leaders of both parties acting as judges. This study discussed about the position of crime resolution institutions in indigenous peoples in the perspective of identity politics and the reassessing the position of crime resolution institutions in indigenous peoples, certainly cannot be separated from the recognition of identity with all the structures and positions of indigenous peoples themselves. This study was designed by using normative legal research approach. The results show that efforts to reassess the position of crime resolution institutions in indigenous peoples, of course, cannot be separated from the recognition of identity with all the structures and positions of indigenous peoples themselves. However, the dominance arising from the resolution of indigenous peoples' crimes is still determined by cultures that are patriarchal, rigid and as if forced from above so as to ignore dialogue both from perpetrators and victims, so that the measure used is the perspective of tribal leaders. However, domination is believed to restore order, order and harmony, but there is one neglected value of ethical legitimacy, namely justice. Therefore, the resolution of crimes against indigenous peoples does not all distribute justice to all parties.